Metode Studi Fikih Kontemporer Telaah Pemikiran Muhammad Syahrur - Hamdan, Muhammad (Jurnal Landraad, 2024)
Contemporary jurisprudence explains that many cases, problems and legal processes must not be confronted with the text's arguments in an opposing way, and solutions must be sought in ijtihad. The purpose of this article is to see how Muhamamd Syahrur created a method for studying contemporary jurisprudence. The method in this article is library research, which carries out library analysis. The results of this research are that Muhammad Syahrur has 2 methods, namely the core of understanding Shahrur's thinking in the context of legal istibaht. First, linguistic and semantic analysis relating to the language and linguistics of the Al-Quran which basically means there is no synonymy, Intratextual/Rejection of atomization and Composition (an-Nazhm).